2009
DOI: 10.1213/ane.0b013e3181935aa5
|View full text |Cite
|
Sign up to set email alerts
|

Relative Analgesic Potencies of Levobupivacaine and Ropivacaine for Caudal Anesthesia in Children

Abstract: In children receiving one minimum alveolar anesthetic concentration of sevoflurane, there were no significant differences in the ED(50) for caudal levobupivacaine and ropivacaine. The potency ratio at ED(50) was 0.92 and 0.89 at ED(95), indicating that caudal levobupivacaine and ropivacaine have a similar potency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 28 publications
0
24
2
1
Order By: Relevance
“…4 -6,8 The type of block may also have an influence on the potency ratio between these 2 drugs, because clinical equipotency has mainly been demonstrated in patients undergoing epidural analgesia. [13][14][15] The clinically relevant finding of this study is the nearly 50% longer analgesia provided by the injection of 20 mL levobupivacaine 0.5% around the posterior sciatic nerve compared with the same dose of ropivacaine. Therefore, levobupivacaine should be considered when postoperative analgesia is required for foot and ankle surgery.…”
Section: Discussionmentioning
confidence: 72%
“…4 -6,8 The type of block may also have an influence on the potency ratio between these 2 drugs, because clinical equipotency has mainly been demonstrated in patients undergoing epidural analgesia. [13][14][15] The clinically relevant finding of this study is the nearly 50% longer analgesia provided by the injection of 20 mL levobupivacaine 0.5% around the posterior sciatic nerve compared with the same dose of ropivacaine. Therefore, levobupivacaine should be considered when postoperative analgesia is required for foot and ankle surgery.…”
Section: Discussionmentioning
confidence: 72%
“…17 Chandran et al compared 0.75% ropivacaine and 0.5% bupivacaine epidurally, and concluded that there were no significant differences in the block parameters but ropivacaine was associated with relatively longer duration of postoperative analgesia. 18 In 2004, Cline et al 19 compared 0.5% levobupivacaine and 0.5% ropivacaine in combination with 1:200,000 epinephrine for axillary brachial plexus block, and found that sensory analgesia was significantly longer with levobupivacaine than with ropivacaine, but ropivacaine patients showed a faster recovery of motor function.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore a recent study showed that there were no significant differences in the ed 50 for caudal levobupivacaine and ropivacaine; the potency ratio at ed 50 was 0.92 and 0.89 at ed 95 , indicating that caudal levobupivacaine and ropivacaine have a similar potency. 30 As for the volume of administration of the local anaesthetic solution, we always used the same volume, in accordance with the literature, 16,17,26,30 for two reasons. Firstly, all surgery procedures falling within the t12 -t10 methamers appear well covered by an injection of 1ml/kg of the local anaesthetic solution, if given through the caudal technique.…”
Section: Discussionmentioning
confidence: 99%